PENGEMBANGAN KOSA KATA BAHASA INGGRIS ANAK USIA DINI LABELING BENDA-BENDA TAMAN KANAK-KANAK PADANG - Darmiati, Darmiati (Universitas Negeri Padang, 2012)
English vocabulary development in children recognize objects in classrooms is still low. This study aims to increase the child's vocabulary familiar objects in English by Kindergarten labelingdi Padang. This type of research is a classroom action research, data collection techniques that researchers conduct observed data through observation / observation and the result is written in the format of observation, documentation, and interviews to strengthen the results of observations made. From the results of this study concluded that the success rate of the game labeling is done in kindergarten Padang in child vocabulary development is relatively good. Thus the presence of media in the form of learning the game labeling or label objects existing classrooms can be used as an alternative form of the game to increase the child's vocabulary development in English.